Analisis Strategi Pengembangan Situs Cagar Budaya Gunung Padang Sebagai Destinasi Wisata dan Peninggalan Sejarah Kebudayaan - Faizal Hamzah; Hary Hermawan; Debi Srinatami (Media Wisata, 2021)
Mountain Heritage Site Padang has a huge potential ranging from its functions, values, and history as a cultural heritage, but behind the potential site of Gunung Padang heritage sites still need to create an optimal development strategy. The research method used in this study is a qualitative research method that whilst the description method, data collection is done by the interview methods of observation and documentation then analysis used in this study using a SWOT analysis so that it will eventually produce a strategy of the analysis results using the SWOT matrix. From the results of the research can be known that the right strategy that must be run on the site of Gunung Padang Cultural Reserve is a strategy that utilizes strengths through opportunities that exist so as to cover the various weaknesses that exist, the strategy can include the development of tourism facilities and infrastructure, service system, preservation site of cultural conservation, and improve the media promotion